How Experiential Quality and Destination Value Shape Experiential Satisfaction and Post-Visit Behavior in Sports and Tourism? - Erdiansyah; Mursalin; Akila; Suhada; Muhammad Eid Balbaa; Mohammed Aljuaid; Rohit Bansal; Asyraf Afthanorhan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The field of sports tourism has witnessed significant growth in the tourism sector, as destinations try to attract visitors through major events such as marathons, soccer games, international competitions, and more. Sports tourism longevity is dependent on the consistent involvement of tourists who actually engage in sports activities. Consequently, this can lead to economic growth within host regions, which might have long-term consequences for the local population. This study analyzes the impact of experiential quality and destination value on experiential satisfaction and post-visit behavior among Indonesian sports event tourists. A survey of 451 sports event tourists was conducted using purposive sampling techniques, with data analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that destination value is significantly influenced by experiential quality, experiential satisfaction, and destination post-visit behavior. In this context, we further investigated how destination value affects experiential satisfaction and post-visit behavior from the perspective of media planning managers. Moreover, experiential satisfaction has a mediating effect between destination value and post–visit behavior, which plays an important role in shaping intentions to revisit or recommend the tourist location. These outcomes provide useful implications for sports tourism managers in Indonesia to improve customer satisfaction and advance their national sports tourism industry.